Pemodelan Sistem E-Voting Pemilihan Presiden Mahasiswa Berbasis Web - Zuhri Ramadhan (Jurnal Teknik dan Informatika, 2019)
Electronic voting (e-voting) can be an alternative solution to replace the conventional Student presidential election currently used at Universitas Pembangunan Panca Budi. By using of information technology in the voting process is supposed to resolve existing problems, such as the voters listed and registration, the complexity of counting the ballots. This research it is propose to carry out the elections of Studentpresidential by utilizing web-based technology. Firstly, E-voting can be access only by student who have student identity card as access right to use the system for log in with username and password then register as voters. Secondly, to vote the candidates, the voters only have once chance to choosing candidates by click on one of picture of candidates on web interface. Overall, after the election period is ends. The data from the database of e-voting system can be immediately obtained by election committee and the data is ready to use as real count of election results without any invalid ballots.